Wzgórze w świetle afazji podkorowych - Rutkiewicz-Hanczewska, Małgorzata; Piątek, Anna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2019)
The article is devoted to the specific nature of subcortical aphasia, with particular emphasis on thalamic aphasia. It describes the features of subcortical aphasias which make it possible to differentiate them from cortical aphasias and defines the characteristics of thalamic aphasia which are indicated by researchers seeking its constitutive features. The article also discusses the anatomic aspects of the thalamus and the latest reports on the functions it performs in the language processing process through thalamocortical networks.